A novel antibacterial and biocompatible Ta-Ag coating fabricated by cold spray technology - Lupoi, Rocco (My University, 2023)
Infection caused by bacterial contamination is a critical problem challenging the successful use of medical implants in orthopaedic and dental applications. Consequently, medical implants with antibacterial abilities are in high demand. Tantalum and silver have been previously characterized to have excellent biocompatibility and antibacterial ability, but due to their significantly different properties, it is challenging to manufacture Ta-Ag components via thermal processing methods. Herein, by taking advantage of the unique characteristics of cold spray (CS) technology, an antibacterial Ta-Ag coating was successfully fabricated for the first time. In the CS process, blended Ta-Ag powders with different Ag concentrations were used to fabricate CS Ta-Ag coatings. Their antibacterial ability was preliminary tested and deposition behaviour was systematically investigated. The coating significantly reduced the metabolic activity of S. aureus bacteria, and a better deposition efficiency was obtained by blended Ta-Ag powder. It was found that soft Ag could aggregate in the coating and hard Ta particles were prone to rebound, which induced the peening effect for Ag and mass loss of Ta in the final coating Moreover, the clue of metallurgy bonding between Ta and Ag was detected in the region that experienced severe deformation despite their immiscibility.
International Thermal Spray Conference 2023 (ITSC 2023)